Conceptual Dimensions and Boundaries of Participation in Organizations: A Critical Evaluation - Dachler, H. Peter; Wilpert, Bernhard (Administrative Science Quarterly, 1978)
This paper outlines a broad conceptual framework for participation in organizations, which provides an overview of four defining dimensions of participatory social arrangements in organizations and their often complex interdependencies. The dimensions of participation discussed in this paper include the social theories underlying participatory social systems and the values and goals each of them implies for participation, the major properties of participatory systems, the outcomes of participation in organizations, and the contextual characteristics of participatory systems which limit or enhance their potential. The view of participation presented in this paper is of a multidimensional, dynamic social phenomenon, the study of which transcends questions unique to any given discipline paradigm and which requires an integration of micro and macro questions. The implications of this conceptualization for theory building, research, and methodology are briefly discussed.